Književna vzgoja v vrtcu ali česa naj se o književnosti naučijo otroci v otroškem vrtcu - Kordigel Aberšek, Metka (Jezik in slovstvo, 1997)
Encounters with children's literature in the pre-school period should be spontaneous and directed towards a creative voyage through literary worlds, but at the same time aiming at stimulating the child's receptive ability which would help him or her experience a literary work in all its aesthetic and emotional intensity. In literary didactics, objectives of literary education are classified as educational, functional and formative. The article focuses on the educational objectives of kindergarten literary education. Three groups of educational objectives are defined: (a) to be able to identify the communicative situation in reception of children's literature (which seems relevant for selecting an appropriate listening strategy); (b) tobe able to identify formal properties of certain literary genres (which seems relevant for production of appropriate mind patterns and thus (co)formation of horizons of expectations); and (c) to get acquainted with the canon of children's literature (which is relevant in terms of learning bothabout national identity and about the fundamental works of Slovene and world literature for children)
Keywords: mladinska književnost; young adult literature; književna vzgoja; vrtci